Contribuição ao estudo de argamassas de emboço com aditivo incorporador de ar - Biava, Juceane de Fátima (2017)
Air-entraining additives have been widely used to improve the properties of coating mortars in the plastic and hardened state. Some of the benefits obtained with the use of mortar additive are improvements in durability, workability, cohesion, compressive strength, tensile strength, plasticity, water retention, segregation, exudation and thermal performance. The incorporated air also attenuates problems caused by any irregular distribution of the aggregates, since the incorporated air bubbles complete the granulometry when it is inadequate, improving the packing and filling the voids, thus reducing the permeability. The reduction of the mortar density, provided by the built-in air microbubbles, produces a larger volume of mortar with the same amount of material used, when compared to mixtures without additive. Therefore, mortars with built-in air have higher yield and, due to the greater ease of application along with the reduction of the weight imposed on the structure and foundations, may represent some economy when the final costs are concerned. This work proposes to contribute to these studies by analyzing the properties of mortars made with crushing sand and natural sand in a fresh and hardened state. For the experimental program, 36 mixtures were produced, in which small aggregates of natural origin and from crushing of basaltic rocks (both passed through the 2,36 mm sieve) were used. Three mass traces (1:4.5, 1:5.0 and 1:5.5) were used, to which was added anionic additive varying from 0% to 0.5%. The mortars were tested in the fresh state for workability, air content, water content and consistency index, mass density and water retention. In the hardened state they were tested for tensile strength in flexion, compression and traction adhesion. In addition, absorption by capillarity, capillary coefficient and bulk density were determined. The influence of the additive content on the tested properties, the thermal performance, the influence of the aggregate type on mortars’ incorporation of air and the cost of the mortars were all also analyzed. Our results suggested a strong relationship between the properties tested and the amount of air-entraining additive added. It was observed that, in mortars produced with crushing sand, there was less air entrained and consequently, the mechanical resistances reached higher values. With the increase of the additive content, there was a lowering in the mechanical resistances, and in the apparent density. Regarding the thermal performance, the samples did not show any significant differences with the increase of the additive content. A lot of mortars, which seemed to be satisfactory regarding the lab tests, showed low performances when applied to substrates, in a way that it wasn’t possible to use them. This drove to consider being necessary a more systemic approach to draw exact conclusions.